Preparation of selenyl 1, 3-oxazines via PhICl2/Cu2O-promoted aminoselenation of O-homoallyl benzimidates with diselenides. Issue 94 (12th November 2021) - Zhang, Linlin; Qi, Lin; Chen, Jia-Min; Dong, Wei; Fang, Zhuo-Yue; Cao, Tong-Yang; Li, Wei; Wang, Li-Jing
Abstract : A practical electrophilic aminoselenation of O -homoallyl benzimidate with diselenides promoted by PhICl2 /Cu2 O has been developed. Various selenyl 1, 3-oxazines were easily obtained in moderate to good yields for the first time. Abstract : A practical electrophilic aminoselenation of O -homoallyl benzimidate with diselenides promoted by PhICl2 /Cu2 O has been developed. The easily available and stable diselenides were used as selenium sources. Various selenyl 1, 3-oxazines, which are important frameworks in medicinal and biological chemistry, were easily obtained in moderate to good yields for the first time. Easy scaleup and scalability make this method attractive for the preparation of other valuable organoselenides.